Kepemimpinan, Kepuasan Kerja, Komitmen Organisasional Terhadap Keinginan Keluar Karyawan - Tamengkel, Lucky F.; Rumawas, Wehelmina (Sam Ratulangi University, 2021)
The high turnover rate is an important issue in the tourism and accommodation sector in which the most significant factor is human resources. This study aims to analyse the effect of transformational leadership, job satisfaction, organizational commitment on employee intention to leave. This study used a survey method with a quantitative descriptive approach. The sample in this study were 174 hotel employees in North Sulawesi Province. Data were collected using a questionnaire, then analysed using a structural equation model (SEM). The results showed that transformational leadership has a positive and significant effect on employee job satisfaction, transformational leadership has a positive and significant effect on organizational commitment, transformational leadership has a negative and significant effect on employee intention to leave, job satisfaction has a negative and significant effect on employee intention to leave, and commitment organizational has a negative and significant effect on employee intention to leave.Â